Several grain dietary patterns are associated with better diet quality and improved shortfall nutrient intakes in US children and adolescents: a study focusing on the 2015–2020 Dietary Guidelines for Americans - Papanikolaou, Yanni (Nutr J, 2017)
BACKGROUND: The present study identified the most commonly consumed grain food patterns in US children and adolescents (2–18 years-old; N = 8,367) relative to those not consuming grains and compared diet quality and nutrient intakes, with focus on 2015–2020 Dietary Guidelines for Americans (2015–2020 DGA) shortfall nutrients. METHODS: Cluster analysis using data from the National Health and Nutrition Examination Survey 2005–2010, identified 8 unique grain food patterns: a) no consumption of main grain groups, b) cakes, cookies and pies, c) yeast bread and rolls, d) cereals, e) pasta, cooked cereals and rice, f) crackers and salty snacks, g) pancakes, waffles and French toast and other grains, and h) quick breads. RESULTS: Energy intake was higher for all grain cluster patterns examined, except ‘cereals’, compared to no grains. Children and adolescents in the ‘yeast bread and rolls’, ‘cereals’, ‘pasta, cooked cereals and rice’, and ‘crackers and salty snacks’ patterns had a higher diet quality relative to no grains (all p < 0.01). Energy adjusted (EA) dietary fiber intake was greater in five of the seven grain patterns, ranging from 1.8 – 2.8 g more per day (all p < 0.01), as compared to those consuming no grains. All grain patterns, except cakes, cookies and pies had higher EA daily folate relative to children in the no grains pattern (all p < 0.0001). EA total fat was lower in ‘cereals’, ‘pasta, cooked cereals and rice’, and ‘pancakes, waffles, French toast and other grains’ in comparison to the no grains food pattern (all p < 0.01). EA magnesium intakes were greater in children and adolescents consuming ‘yeast bread and rolls’, ‘pasta, cooked cereals and rice’, and ‘quick breads’, while EA iron was higher in all grain patterns relative to no grains (all p < 0.01). EA vitamin D intake was higher only in children consuming ‘cereals’ vs. no grain group (p < 0.0001). There were no significant differences in total or added sugar intake across all grain clusters as compared to no grains. CONCLUSIONS: Consumption of several, but not all, grain food patterns in children and adolescents were associated with improved 2015–2020 DGA shortfall nutrient intakes and diet quality as compared to those consuming no grains.